„Momenty wychowawcze” w projektowaniu procesu kształcenia kulturowej kompetencji dzieci - Monika Wiśniewska-Kin (Problemy Wczesnej Edukacji)
The article presents the results of an educational research project implemented in the school year 2018/2019 in selected primary schools in urban environment (Łódź). The aim of the study was to diagnose Janusz Korczak’s “educational moments” in designing the process of developing cultural competence. The investigator appeared in the role participant as an observer (the researcher came from the examined environment and had the opportunity to “blend into” the events). The material came from participant observation. The observation embraced practical and socio-cognitive activity of the pupils. The results allow recognition in how a child, applying language, marks its being in the world, how it acts via language, how it uses language to reach the mysteries of the world and what it does with language during this operation. The final comment suggests that school is there to help a child to interpret the world, to recognize various phenomena, to assume attitudes towards them, and to make their independent evaluation.